STUDIES ON THE EFFECT OF GROUNDNUT (ARACHIS HYPogaea L.) ON THE Fertility OF ARID ZONE SOILS - Bhan, Suraj; Misra, D K (Annals of Arid Zone, 2016)
In experiments conducted at the Central Arid Zone Research Institute, Jodhpur during 1966 to 1968 groundout cultivation improved the fertility of soil in terms of increased organic carbon and nitrogen content and ultimately increased the yield of succeeding crop of bajra by 21.5 per cent. Erect variety 'A. K. 12-24' grown in 45 to to cm wide rows considerably reduced the erosion losses and thus maintained the soil fertility. Erosion losses were further reduced when groundnut was grown between permanent grass strips where a strip width of 20 metre for the former and 5 metre for the latter was adopted. Zizyphu8 mulch over the groundnut harvested plots also proved as an equally effective measure in minimising erosion losses.